A study on training factors and its impact on training effectiveness towards technical workers in Majlis Perbandaran Johor Bahru Tengah / Nur Hazirah Mohd Sapuan - Mohd Sapuan, Nur Hazirah (Faculty of Business and Management, 2014)
The main objective of this study is to determine the impact of training factors on training effectiveness towards technical workers in an organization. The main variables examined in this research are trainees’ characteristics (ages, genders, marital status, education levels and length of working), training environment, work environment and type of training. The instrument used to study the impact of training factors on training effectiveness is questionnaires which were distributed to 105 respondents in Majlis Perbandaran Johor Bahru Tengah, Johor Bahru, Johor. Through this study, organizations able to improve their level understanding on designing effective training that able to help organization in achieving training objective successfully as well as improving organization and employees performance.